Centaurea dolopica (Asteraceae, Cardueae), a new species of section Acrocentron from Greece - Zografidis, Aris; Koutroumpa, Konstantina; Liveri, Eleni; Dimopoulos, Panayotis (Phytotaxa, 2023)
Centaurea dolopica from Omvriaki area in Central Greece is described and illustrated as a species new to science based on morphological and molecular evidence. Detailed description of the new species, distribution, ecology, conservation status, as well as comparison with closely related species are provided. Individuals of Centaurea dolopica were also examined karyologically resulting to the chromosome number 2n = 2x = 22 accompanied by comprehensive karyotype analysis. Phylogenetic study including the new species and major representatives of Centaurea section Acrocentron was conducted using two nuclear markers (ITS, ETS). The results revealed the placement of Centaurea dolopica in the Greek-Aegean clade of the section in close evolutionary relationship with the members of the C. achaia group, corroborating the morphological and karyological data.